O-087 Embryos with higher mitochondrial DNA ratios show better clinical outcomes in single euploid embryo transfer. (6th August 2021) - Chen, D; Kao, C W
Abstract: Study question: To assess whether there is a relationship between mitochondrial DNA content and implantation result. Summary answer: The embryos with a higher mitochondrial DNA ratio increase pregnancy rate and implantation rate in single euploid embryo transfer. What is known already: Mitochondria is an important organelle that generates energy during embryonic development. Recent literature points out that mitochondrial content and function may be related to implantation success and embryo viability. Some studies have linked increased ratios of mitochondrial DNA to aneuploidy, advanced maternal age, and euploid blastocyst with implantation failure, while others have failed to demonstrate similar findings. Study design, size, duration: This study is a retrospective cohort study from 2016 to 2019, including 1465 single embryo transfer cycles. Participants/materials, setting, methods: The involved embryos were biopsied on Day 5 or 6 and the mitochondrial DNA ratio of 1465 embryos was examined undergoing PGS/NGS. The mitochondrial DNA ratios were normalized for technical batch-to-batch variation. The mitochondrial DNA ratio between the implantation group and non-implantation group was statistically analyzed. Data were analyzed by the student's t-test for continuous variables and Chi-square test for categorical variables. Main results and the role of chance: The mitochondrial DNA ratio of embryos was no significant difference between different age spans ( p = 0.772) and ploidy (p = 0.224). D5 biopsied embryos, however, contained a significantly higher mitochondrial DNA ratio than D6 biopsied embryos (p < 0.0001). All of the single embryo transferred embryos were classified into two groups; implanted and non-implanted embryos. Results from 1465 transferred embryos show that the mitochondrial DNA ratio of implanted embryos was statistically significantly higher than non-implanted embryos (p = 0.0053). Besides, the cut-off values were established, dividing the transferred embryos into high and low mitochondrial DNA ratio groups. The pregnancy rate and implantation rate of the high mitochondrial DNA ratio group was higher than the low mitochondrial DNA ratio group: [Pregnancy rate] 74% vs. 63.5% (p = 0.0209); [Implantation rate] 57.3% vs. 50.8% (p = 0.1907). Limitations, reasons for caution: The mitochondrial DNA ratios were analyzed by bioinformatics processing in Miseq reporter software (Illumina) files in the BAM and FASTQ format. Not sure if there is reproducibility in different sequencing platforms. Wider implications of the findings: There still remains a lack of clarity regarding the relationship between mitochondrial function and transfer outcome. This retrospective study links an association between increased mtDNA content and increased implantation. Trial registration number: not applicable